PENGARUH KUALITAS PELAYANAN DAN CITRA INSTITUSI TERHADAP KEPUASAN PENGGUNA JASA RSUD KOTA MADIUN - Afriza Tri Effendi; Ali Djamhuri (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this study is to determine the effect of service quality and image of the institution to the satisfaction of patients either simultaneously or partially. The dependent variable used in this study is patient’s satisfaction. Independent variables used in this study are service quality and the image of the institution. This study used a 100 sample of RSUD Madiun’s patients with the simple random sampling method. The method of analyzing data used is multiple linear regression analysis. From the regression analysis it is found that the quality of service and the image of the institution simultaneously effect patient’s satisfaction. Service quality partially affect patient satisfaction, as well as the image of the institution. Keywords: service quality, the image of the institution and patient satisfaction